A Sistematic Literatur Review: Women in Science Education and Social Welfare - Bayu Anshor Mursalin; Vivin Tarbiyah; Winda Fadhila Saputri (WISE Pendidikan Indonesia, 2025)
This study presents a systematic literature review (SLR) that examines the interrelationship between women’s participation in science education and its contribution to social welfare within the context of sustainable development. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, covering international databases such as Scopus, Web of Science, Taylor & Francis, SpringerLink, SAGE Journals, and ScienceDirect, as well as open-access repositories indexed in SINTA for publications between 2020 and 2024. A total of 153 records were initially identified, and through a rigorous screening process, 10 high quality studies were selected for synthesis. The findings reveal three convergent domains: (1) cognitive and motivational development through education, (2) structural empowerment via inclusive and gender-responsive STEM curricula, and (3) socio-economic advancement mediated by leadership and entrepreneurship training. These studies collectively demonstrate that science education serves as a transformative mechanism that enhances women’s confidence, agency, and social responsibility while strengthening their roles as contributors to community welfare. Furthermore, the review underscores that access to science education not only narrows gender disparities in STEM but also generates ripple effects on family well-being, environmental stewardship, and sustainable livelihoods. By integrating insights from global and regional contexts, this study proposes an interdisciplinary framework positioning women’s education as a bridge between cognitive emancipation and social transformation. The findings imply that policies promoting gender-responsive science education, mentorship, and digital inclusion are essential to empower women as agents of innovation and welfare, thereby fostering equitable and sustainable human development.